Interpretacija baštine za održivi razvoj Bosne i Hercegovine / Interpretation of Heritage for Sustainable Development of Bosnia and Herzegovina - Hebib, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
This text is a review of a book by Zoran Bibanović Bosnia and Herzegovina. Cultural Gate of Europe, Library National Treasure of Bosnia and Herzegovina, Sarajevo, 2023, presented delivered at the presentation held at the Bosnian Cultural Center in Sarajevo on 29 February 2024.